The secrets of Buddhist meditation : visionary meditation texts from early medieval China - Greene, Eric M. (Classics in East Asian Buddhism., 2021)
"In the early 400s, numerous Indian and Central Asian Buddhist "meditation masters" (chanshi) traveled to China, where they established the first enduring traditions of Buddhist meditation practice in East Asia. The forms of contemplative practice that these missionaries brought with them, and which their Chinese students further developed, remained for several centuries the basic understanding of "meditation" (chan) in China. Although modern scholars and readers have long been familiar with the approaches to meditation of the Chan (Zen) School that later became so popular throughout East Asia, these earlier and in some ways more pervasive forms of practice have long been overlooked or ignored. This volume presents a comprehensive study of the content and historical formation, as well as complete English translations, of two of the most influential manuals in which these approaches to Buddhist meditation are discussed: the Scripture on the Secret Essential Methods of Chan (Chan Essentials) and the Secret Methods for Curing Chan Sickness (Methods for Curing). Translated here into English for the first time, these documents reveal a distinctly visionary form of Buddhist meditation whose goal is the acquisition of concrete, symbolic visions attesting to the practitioner's purity and progress toward liberation. Both texts are "apocryphal" scriptures: Taking the form of Indian Buddhist sutras translated into Chinese, they were in fact new compositions, written or at least assembled in China in the first half of the fifth century. Though written in China, their historical significance extends beyond the East Asian context as they are among the earliest written sources anywhere to record certain kinds of information about Buddhist meditation that hitherto had been the preserve of oral tradition and personal initiation. To this extent they indeed divulge, as their titles claim, the "secrets" of Buddhist meditation. Through them, we witness a culture of Buddhist meditation that has remained largely unknown but which for many centuries was widely shared across North India, Central Asia, and China"--